2021
DOI: 10.1186/s13058-021-01431-w
|View full text |Cite
|
Sign up to set email alerts
|

Lasofoxifene as a potential treatment for therapy-resistant ER-positive metastatic breast cancer

Abstract: Background Endocrine therapy remains the mainstay of treatment for estrogen receptor-positive (ER+) breast cancer. Constitutively active mutations in the ligand binding domain of ERα render tumors resistant to endocrine agents. Breast cancers with the two most common ERα mutations, Y537S and D538G, have low sensitivity to fulvestrant inhibition, a typical second-line endocrine therapy. Lasofoxifene is a selective estrogen receptor modulator with benefits on bone health and breast cancer prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 37 publications
1
43
0
1
Order By: Relevance
“…Likewise, the RU39411 structures show similar H12 conformational changes with H12 moving closer to the AF2 cleft in the Y537S vs WT (Figure 7C). We previously observed similar WT and Y537S structures for lasofoxifene, which also maintains significant transcriptional inhibitory activities 28 . For LA-Deg, its 3R-methylpyrrolidine points towards the H11-12 loop and H12 is less ordered, similar to other SERDs 26 .…”
Section: Structural Basis Of Improved Antagonism For Y537s Erαmentioning
confidence: 60%
See 3 more Smart Citations
“…Likewise, the RU39411 structures show similar H12 conformational changes with H12 moving closer to the AF2 cleft in the Y537S vs WT (Figure 7C). We previously observed similar WT and Y537S structures for lasofoxifene, which also maintains significant transcriptional inhibitory activities 28 . For LA-Deg, its 3R-methylpyrrolidine points towards the H11-12 loop and H12 is less ordered, similar to other SERDs 26 .…”
Section: Structural Basis Of Improved Antagonism For Y537s Erαmentioning
confidence: 60%
“…Importantly, we also showed that enforcing H12 burial in the AF-2 cleft improves transcriptional antagonistic activities on a reporter vector in breast cancer cells harboring WT/Y537S ESR1. Our studies, combined with the recent work from the McDonnell Laboratory showing that transcriptional antagonism contributes most of fulvestrant's therapeutic activities independent of maximal receptor depletion 31 , and the observed significant efficacy of the SERM/SERD lasofoxifene for the Y537S mutant 28 , suggest that future antiestrogen development efforts for treatment of tumors with constitutively active mutations should focus on maximizing transcriptional antagonistic activities.…”
Section: Cellular Proliferation Assays In Mcf7 Cells With Wt/y537s Esr1 Were Used To Reveal the Role Of Inducedmentioning
confidence: 61%
See 2 more Smart Citations
“…He then moved on to his recent and novel discoveries of ESR1 mutations in metastatic breast cancers [ 4 ] and the use of new selective estrogen receptor modulators (SERMs) to target them. He also showed data from the mammary intraductal model (MIND), a variant of the patient-derived xenograft (PDX) animal model that has led to new clinical trials of lasofoxifene [ 5 ]. In addition, he is currently studying the potential protective benefit of a recently approved hormone replacement therapy that combines an estrogen with a SERM.…”
mentioning
confidence: 99%